2004
DOI: 10.1785/0120030107
|View full text |Cite
|
Sign up to set email alerts
|

Plate-Tectonic Analysis of Shallow Seismicity: Apparent Boundary Width, Beta, Corner Magnitude, Coupled Lithosphere Thickness, and Coupling in Seven Tectonic Settings

Abstract: A new plate model is used to analyze the mean seismicities of seven types of plate boundary (CRB, continental rift boundary; CTF, continental transform fault; CCB, continental convergent boundary; OSR, oceanic spreading ridge; OTF, oceanic transform fault; OCB, oceanic convergent boundary; SUB, subduction zone). We compare the platelike (nonorogen) regions of model PB2002 (Bird, 2003) with the centroid moment tensor (CMT) catalog to select apparent boundary half-widths and then assign 95% of shallow earthquake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
352
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 249 publications
(371 citation statements)
references
References 45 publications
15
352
4
Order By: Relevance
“…BIRD and KAGAN (2004) found that the main difference between earthquakes in different geological settings were with their estimates of a and M C for each setting. In the case of subduction zone earthquakes, BIRD and KAGAN (2004) argued that there is no statistically significant justification for subdividing the subduction zone setting into smaller subsets (e.g., subduction zones subducting old crust versus subduction zones subducting new crust). The only effect they noticed was that a increases with the rate of subduction (i.e., how fast the plates were moving closer together).…”
Section: Earthquake Frequencymentioning
confidence: 94%
See 4 more Smart Citations
“…BIRD and KAGAN (2004) found that the main difference between earthquakes in different geological settings were with their estimates of a and M C for each setting. In the case of subduction zone earthquakes, BIRD and KAGAN (2004) argued that there is no statistically significant justification for subdividing the subduction zone setting into smaller subsets (e.g., subduction zones subducting old crust versus subduction zones subducting new crust). The only effect they noticed was that a increases with the rate of subduction (i.e., how fast the plates were moving closer together).…”
Section: Earthquake Frequencymentioning
confidence: 94%
“…Cooler temperatures would also lead to higher densities, lower buoyancy and potentially weaker coupling which may also influence the maximum magnitude and/or rate of seismic moment release. On the other hand, other studies suggest there is little dependence of subduction zone seismicity (rate or maximum magnitude) on plate age (BIRD and KAGAN, 2004;NISHENKO, 1991;PACHECO et al, 1993), in which case there is no basis for inferring that magnitude 9 earthquakes cannot occur off Java. WELLS et al (2003) have argued that the presence of sedimentary basins between the trench and the coast (the forearc of the subduction zone) correlates with regions of increased megathrust earthquake slip, and since Java and Sumatra both have well developed forearc basins (see, e.g., the seismic reflection profiles of KOPP, 2002), it might be argued that both can host very large earthquakes.…”
Section: Javamentioning
confidence: 98%
See 3 more Smart Citations